Political Representation Among Young Voters: Analysis of Students' Political Preferences in the 2024 West Java Regional Election - Diani, Diani Dewi Saila; Karim Suryadi; Vini Agustiani Hadia (Academic Solution Publisher, 2025)
Political participation among young citizens in regional head elections has become a crucial element in strengthening local democracy in Indonesia. This study aims to analyze the political preferences of young voters in the 2024 West Java Pilkada and identify the factors influencing their decision-making processes. Using a qualitative case study approach, data were collected through in-depth interviews, observation, and documentation involving 12 students of the Indonesian Education University (UPI) who represent active voters in campus-based political activities. Data were analyzed through thematic analysis to identify dominant patterns in voter behavior. The findings reveal that young voters tend to prioritize candidates’ track records, leadership experience, clear vision and mission, and realistic work programs, particularly those related to education, employment, and community welfare. They also consider the credibility of supporting political parties and the educational background of candidates as indicators of competence. These results indicate a shift towards more rational, critical, and issue-oriented political preferences among young voters. This study highlights the growing political awareness of younger generations and offers insights into how youth perspectives may influence regional policymaking in the future.